Evolutionary profile of patients with hemoglobin SC disease regularly followed in Côte d'Ivoire - Méité, N'dogomo; Nanho, Clotaire D.; Sangaré, Mahawa; Kouakou, Boidy; Kamara, Ismael; Silué, Alexis D.; Packo, Saint-cyr; Botti, Renée P.; N’dahtz, Emeraude; Koffi, Gustave K.; Sanogo, Ibrahima (International Journal of Research in Medical Sciences, 2018)
Background: West Africa is recognized as the elective focus of hemoglobin C. The S and C combination in the same patient gives a major sickle cell syndrome. In our country, very few series dealing with the evolutionary features of this SC form have been published contrary to the homozygous SS form. The aim of this study was to describe the evolutionary profile of double heterozygous SC sickle cell patients. Methods: This was a retrospective and prospective study with descriptive and analytical purpose of 174 SC sickle cell patients. Results: The median age was 26 years with extremes of 6 years and 57 years. 96% of patients had less than 4 vaso-occlusive seizures per year. The evolutionary complications were mainly ischemic (56.30%) and infectious (39.10%). Among ischemic complications, sickle cell retinopathies and aseptic osteonecrosis are the most common with 59.20% and 31.63% respectively. Infectious complications were dominated by ENT (36.76%) and osteoarticular (35.29%) infections. Only age had an influence on the occurrence of ischemic complications (p = 0.0001). The probability of survival at 5 years was 99.38% and that at 20 years was 91.57%. The overall survival was not influenced by evolutionary complications. Conclusions: Infectious and ischemic evolutionary complications show the importance of vaccination and an early screening program.